Protein and fatty acid contents in meat and eggs of horseshoe crabs from two locations in Melaka - Sabri, Siti Nurain (2015)
A total of 20 samples of adult female horseshoe crabs were collected from Melaka: 10 from Pantai Puteri and another 10 from Pulai to determine nutrient composition of meat and eggs of horseshoe crabs. Meat and eggs of the horseshoe crabs were harvested and processed into 20 meat and 20 egg samples. Morphological measurements of the horseshoe crabs taken were perimeter of prosoma (cephalothorax), length of telson (tail), length of opisthosoma (abdomen), live weight and weight of meat and eggs. For both locations: Pantai Puteri and Pulai all parameters studied showed no significant difference (p>0.05). Means of live weight, perimeter of prosoma, length of telson and length of opisthosoma were 1.7 ± 0.05 kg, 64.9 ± 1.06 cm, 20.4 ± 0.46 cm and 9.0 ± 0.12 cm respectively. Mean meat and egg yields of horseshoe crabs were 2.7 ± 0.22 g and 218.3 ± 27.67 g, respectively. The crude protein analysis revealed that the crude protein of horseshoe crabs was 1.1 ± 0.50% for meat and 17.2 ± 0.77% for eggs. Meat of horseshoe crabs had high saturated fatty acids, followed by unsaturated fatty acids and monoenes. The saturated fatty acids of meat was 54.8 ± 2.92%, unsaturated fatty acids 45.2 ± 2.92%, monoenes 24.4 ± 1.42%, α-Linolenic acid 2.00 ± 0.20% and docosahexaenoic acid 2.51± 0.44%. Eggs of horseshoe crabs had high unsaturated fatty acids, followed by saturated fatty acids and monoenes. The unsaturated fatty acids of eggs was 64.81 ± 0.51%, saturated fatty acids 35.20 ± 0.51%, monoenes 29.03 ± 0.69%, α-Linolenic acid 1.79 ± 0.08% and docosahexaenoic acid 3.39 ± 0.16%. Mean blue blood volume collected was 150 ml per horseshoe crab. It can be concluded that both locations, Pantai Puteri and Pulai, share a similar habitat for horseshoe crabs, thus this could contribute to the similarity in morphological characteristics, crude protein content and fatty acid composition of the horseshoe crabs in the two locations.